The Role of Physical Activity in Improving Quality of Life and Glycemic Control in Type 2 Diabetes Mellitus Patients: A Systematic Literature Review - Citra Trisna; Dian Ayubi (Poltekkes Kemenkes Banten, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic disease that poses a global health burden with a significant increase in cases and complications. Physical activity plays an important role in improving glycemic control and quality of life in T2DM patients. This study aims to analyze the role of physical activity on quality of life and glycemic control through a Systematic Literature Review (SLR) guided by PRISMA. Articles were searched through the PubMed and ScienceDirect databases using the keywords “Diabetes Mellitus Type 2,” “Physical Activity,” and “Quality of Life.” Of the 178 articles found, 11 met the inclusion criteria (English language, published between 2020 and 2025, full text, and studies on DMT2 patients). Most studies used a Randomized Controlled Trial (RCT) design. The synthesis results show that aerobic physical activity, resistance training, or a combination of both consistently improves the quality of life and physical function of patients with DMT2. Structured home-based exercise for 12 weeks and community-based and online programs showed significant improvements in physical, psychological, and social domains. In addition, seven of the eleven studies reported a decrease in blood glucose or HbA1c levels after intervention. Programs with supervision, whether in-person or online, provided better compliance and glycemic outcomes. Conclusion, regular physical activity, especially a supervised combination of aerobic and resistance training, effectively improves the quality of life and metabolic control of patients with type 2 diabetes and has the potential to be integrated into primary and community health services.